Building Resilience Skills among Educational Managers: Latent Content Insights from Talent Development – Training Plans - Obmerga, Marwin; Chung, Lynn; Vergara, Raimeelyn; Soliman, Alma; Ma, Jingwen; Zeng, Yuntong; Cabudol, Emerson (GILE Journal of Skills Development, 2025)
As contemporary educational organisations face persistent operational challenges and evolving institutional demands, cultivating organisational resilience among their managerial ranks has become imperative. Amid rapid disruption and systemic transitions, educational managers encounter multifaceted pressures that necessitate proactive and sustained capacity-building. This study addresses this demand by investigating how organisational resilience is conceptualised and reinforced through Training Plans designed for Talent Development. Grounded in the Theory of Reasoned Action, this qualitative inquiry employed Latent Content Analysis to examine Training Plans formulated by Filipino and Chinese doctoral students, each offering applied insights into dynamic leadership development and institutional adaptability. The analysis revealed three (3) distinct yet interrelated themes: Tempering the Tensions, Treading toward Thriving, and Targeting the Triumphs. These themes underscore the strategies for enhancing resilience across individual, relational, and systemic dimensions of educational management. Central to these findings is the cultivation of conflict navigation, strategic thinking, and outcome-orientation as foundational resilience skills. The study advances theoretical discourse by asserting that resilience-building is not a passive or incidental process but a deliberate endeavour shaped by belief systems and organisational contexts. Practically, the findings inform the design of training initiatives, enabling educational managers to integrate Organisational Development and Human Resource Management principles to sustain agile, responsive, and future-ready institutions.